Is the Washington consensus dead? Growth, openness, and the great liberation, 1970s - 2000s - Antoni Estevadeordal; Alan M. Taylor (Inter-American Development Bank (IDB), 2009)
According to the Washington Consensus, developing countries' growth would benefit from reductions in barriers to trade. However, the empirical basis for judging trade reforms is weak. Econometrics are mostly ad hoc; results are typically not judged against models; policies are poorly measured; and most studies are based on pre-1990 experience. We address these concerns-by using a model based on capital and intermediate goods; by compiling new disaggregated tariff measures; and by employing treatment-and-control analysis. We find that a specific treatment, liberalizing tariffs on imported capital and intermediate goods, did lead to faster growth in a manner consistent with theory.
hdl:11319/2518
Keywords: E65; F10; F13; F43; F53; N10; N70; O40; 330; GATT; Uruguay Round; trade liberalization; growth; capital goods; intermediate goods; developing countries